Factor structure and psychometric properties of the Hungarian version of the Mentalized Affectivity Scale (MAS): A cross-sectional study. - Veronika Bóné; Éva Kalla; Attila Pilinszki (PLoS ONE)
Background There is an increasing need among researchers to explore how emotions are regulated and processed. Mentalized affectivity is a complex cognitive and affective ability to understand thoughts, feelings and intentions of oneself and others. Aims This study proposes a psychometric validation of the Hungarian version of the Mentalized Affectivity Scale (MAS), and measures the three main domains of mentalized emotions: emotion recognition, processing and expression. Materials & methods Participants (N = 316) were recruited using the snowball sampling method via various mailing lists and social networking sites from August 2023 to November 2023. Structural Equation Modeling was used to validate the original factor structure and Principal Component was used for subsequent exploration. We used Spearman's correlation to measure convergent validity and the Kruskal-Wallis test for correlations with demographics. Results Initial confirmatory and exploratory factor analysis on the 60 items of Greenberg did not show satisfactory outcomes. Subsequently, we checked the 35-item version of the scale: after deleting one item, and using the original three-factor structure, we found that the scale showed great internal consistency and sufficient convergent validity to other measured constructs. Discussion & conclusion The Hungarian 34-item Mentalized Affectivity Scale and its three subscales are suitable for measuring mentalized affectivity.